2019
DOI: 10.3390/cells9010022
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 5 Silencing Sensitizes Dopaminergic Neuronal Cells to Rotenone via DNA Damage-Triggered ATM/p53/PUMA Signaling-Mediated Apoptosis

Abstract: Peroxiredoxins (Prxs) are a family of thioredoxin peroxidases. Accumulating evidence suggests that changes in the expression of Prxs may be involved in neurodegenerative diseases pathology. However, the expression and function of Prxs in Parkinson's disease (PD) remains unclear.Here, we showed that Prx5 was the most downregulated of the six Prx subtypes in dopaminergic (DA) neurons in rotenone-induced cellular and rat models of PD, suggesting possible roles in regulating their survival. Depletion of Prx5 sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The p53 enhances the expression of Sestrin1 and Sestrin2 to activate AMPK, thereby preventing mTOR in the nucleus [38,39]. However, p53-induced proapoptotic factors, such as p53-induced BH3-only protein (PUMA), also activate autophagy in the cytoplasm [40]. Follicular atresia was accompanied by apparent DNA damage (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The p53 enhances the expression of Sestrin1 and Sestrin2 to activate AMPK, thereby preventing mTOR in the nucleus [38,39]. However, p53-induced proapoptotic factors, such as p53-induced BH3-only protein (PUMA), also activate autophagy in the cytoplasm [40]. Follicular atresia was accompanied by apparent DNA damage (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this research showed that AJ could reduce the expression of apoptotic genes (p53 and Bax). P53 changes the stability of the mitochondrial membrane, which induces the intracellular matrix inflow of cytochrome c. Thus, these apoptotic factors can control Bax and caspases activities (29). In addition, γ-ray stimulates apoptotic variables in pancreatic cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…For example, upregulation of DNA damage and p53, a powerful pro-apoptotic factor, has been reported in a MPTP-induced mouse model, and p53 inhibition can prevent neurodegeneration and ameliorate motor deficits [ 148 , 149 ]. Similarly, DNA damage and apoptotic phenotypes have been observed in other PD toxin models, as well as transgenic mouse models of PD, although p53 may not always be the mediator of cell death in these paradigms [ 29 , 147 , 150 , 151 , 152 ].…”
Section: Mechanisms Of Dna Damage-mediated Neurotoxicity In Pdmentioning
confidence: 91%